The Influence of Financial Accountability, Organization Size, Population Quality, and Economic Growth on Regional Taxes in Sumatra - Fadlil Usman; Nina Andriana; Muhadi Prabowo; Dini Anggraini (WIM Solusi Prima, 2023)
This research aims to analyze the relationship between financial accountability, organizational size, population quality, and economic growth with local taxes. Indonesia has experienced major fiscal decentralization since 2001. Some regions can obtain better local taxes than other regions. This paper connects local taxes with resources and accountability. These resources consist of physical resources, human resources, and financial resources. This article also estimates the impact of the Covid-19 crisis on local taxes. This research includes 154 districts/cities in Sumatra in the period 2013 to 2021. This research uses a panel method with the Common Effects Model (CEM), Fixed Effects Model (FEM), and Random Effects Model (REM). The findings conclude that financial accountability, organizational size, and population quality influence increasing local tax revenues. Economic growth is also important in supporting increased local taxes. Meanwhile, Covid-19 slowed down the increase in local taxes. The implications of this research imply that local governments must try harder to maximize the use of existing resources in the region. Physical resources can be developed by local governments themselves or provided by the central government. Human resource development must be carried out more quickly. Regional governments must increase their capacity to collect local taxes and maintain accountability to gain public trust.